The Relationship Between Famine Exposure During Early Life and Left Ventricular Hypertrophy in Adulthood - Yan, Yu-qin; Liu, Lin; Sun, Shuo; Feng, Ying-qing; Li, Jie; Huang, Yu-qing (Frontiers in Nutrition, 2022)
Background: Although the evidence was still limited, some studies suggested that childhood malnutrition might affect cardiac function and structure in adulthood. To address the knowledge gap, this study investigated if the Great Chinese Famine exposure during early life has affected left ventricular hypertrophy (LVH). Methods: This research was a cross-sectional study. It included participants who had cardiac ultrasound assessment and were born in Guangdong, China, from 1 October 1952 to 30 September 1964. They were classified according to their exposure period to famine, namely no exposure, fetal-, early-, mid-, and late childhood. Multivariate logistic regression and subgroup analysis have been conducted for determining the odds ratio and confidence intervals between famine exposure and LVH. Results: This research composed 2543 participants, 1612 females, their mean age is 59.07 ± 3.65 years, and 704 had LVH. The LVH prevalence was 122 (23.6%), 87 (25.1%), 133 (27.3%), 184 (29.2%), and 178 (31.7%), in non-, fetal-, early-, mid-, and late-childhood exposed groups, respectively (P=0.031), while in the non-exposed group, the odds ratios for developing carotid plaque as a result of fetal, early-, mid- to late-childhood exposure were 1.08 (95% CI: 0.76, 1.59, P=0.619),1.24 (95% CI: 1.03, 1.79, P=0.031),1.49 (95% CI: 1.10, 2.01, P=0.009), and 1.64 (95% CI: 1.25, 2.18, P=0.001), respectively (P for trend=0.003). There was no interactive effect between gender, obesity, or hypertension history with how the famine influence LVH, as the subgroups analyses demonstrated (all P for interaction > 0.05). Conclusion: This research has demonstrated the potential relationship between Great Chinese Famine exposure during childhood and LVH in adults.